PsycEXTRA Dataset 2013
DOI: 10.1037/e571212013-415
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Violence in Psychosis: Systematic Review and Meta-Regression Analysis of 110 Studies

Abstract: Background: Previous reviews on risk and protective factors for violence in psychosis have produced contrasting findings. There is therefore a need to clarify the direction and strength of association of risk and protective factors for violent outcomes in individuals with psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
4
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(172 citation statements)
references
References 24 publications
9
149
4
10
Order By: Relevance
“…In people with SMI, the significant associations between lifetime violence and male sex, being single, a history of violent victimization and unresponsiveness to treatment (which can be taken to imply the presence of positive symptoms due to the low levels of recognition of negative symptoms in this setting ) are in accordance with other cohort and community-based studies (Elbogen and Johnson, 2009;Silver et al, 2011;Sturup et al, 2011;Witt et al, 2013). In contrast to a recent meta-analysis of 110 studies examining risk factors for violence in people with SMI (Witt et al, 2013), lower socio-economic status, alcohol and drug (khat) use were not associated with violence in our study.…”
Section: Violence and Smisupporting
confidence: 69%
See 1 more Smart Citation
“…In people with SMI, the significant associations between lifetime violence and male sex, being single, a history of violent victimization and unresponsiveness to treatment (which can be taken to imply the presence of positive symptoms due to the low levels of recognition of negative symptoms in this setting ) are in accordance with other cohort and community-based studies (Elbogen and Johnson, 2009;Silver et al, 2011;Sturup et al, 2011;Witt et al, 2013). In contrast to a recent meta-analysis of 110 studies examining risk factors for violence in people with SMI (Witt et al, 2013), lower socio-economic status, alcohol and drug (khat) use were not associated with violence in our study.…”
Section: Violence and Smisupporting
confidence: 69%
“…Factors that could confound any observed observation between SMI and violence or violent victimization were defined prior to the study on the basis of a review of the literature (Witt et al, 2013): is an evergreen plant which contains cathinone, an amphetamine-like stimulant.…”
Section: Potential Confounding Variablesmentioning
confidence: 99%
“…A substantial body of epidemiological, cohort, and case-control studies has shown associations between the risk factors described in this guideline and medium-to long-term relative risk of aggression in populations (Coid et al 2006;Doyle and Dolan 2006;Doyle et al 2012;Elbogen and Johnson 2009;Elbogen et al 2006;Eriksson et al 2011;Falk et al 2014;Harford et al 2013;Swanson et al 1990;Ten Have et al 2014;Van Dorn et al 2012;Whittington et al 2013;Witt et al 2013). However, there is no evidence that assessment of any of these factors can predict aggression in an individual (Buchanan et al 2012;Fazel et al 2012;Large et al 2011b;Rossegger et al 2013;Singh et al 2011Singh et al , 2014Thomas et al 2005).…”
Section: Guideline IV Assessment Of Risk For Aggressive Behaviorsmentioning
confidence: 99%
“…"There is no doubt that inclusion of past behavior improves the prediction of future behavior" [22]. Large scale reviews of the literature have consistently found past history of behavior to be a significant factor in predicting future behavior [21][22][23][24].…”
Section: Anamnestic Actuarial and Clinical Judgementsmentioning
confidence: 99%